A combined theoretical and experimental study on the oxidation of fulvic acid by the sulfate radical anion - David Gara, Pedro Maximiliano (2009)
The kinetics of the reaction of sulfate radicals with the IHSS Waskish peat fulvic acid in water was investigated in the temperature range from 289.2 to 305.2 K. The proposed mechanism considers the reversible binding of the sulfate radicals by the fulvic acid. The kinetic analysis of the data allows the determination of the thermodynamic parameters ΔG° = -10.2 kcal mol-1, ΔH° = -16 kcal mol-1 and ΔS° = -20.3 cal K-1 mol-1 for the reversible association at 298.2 K. Theoretical (DFT) calculations performed with the Buffle model of the fulvic acids support the formation of H-bonded adducts between the inorganic radicals and the humic substances. The experimental enthalpy change compares well with the theoretical values found for some of the investigated adducts.